2020
DOI: 10.1021/acs.chemmater.9b05000
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed Halide Perovskite Single Crystals with Intrinsic Compositional Gradients for X-ray Detection

Abstract: Although epitaxial growth is the fundamental method to realize lattice matched heterojunctions in electronics manufacturing, large-scale epitaxial single crystal layers based on solution-processing have rarely been reported. Here, cascade organic−inorganic hybrid perovskite single crystals with purity quotient over 99.9% consisting of chlorine, bromine, and iodine are fabricated by solution-processed epitaxial growth, in which the mismatch rate between adjacent layers is less than 1%. The area of solution-proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 47 publications
0
76
0
Order By: Relevance
“…Methylammonium lead halide perovskites (MAPbX 3 , where X = Cl, Br, I) have been the most widely studied OIHPs (Wei et al, 2017;Jiang et al, 2019) and the lattice parameters of MAPbI 3 and MAPbBr 3 are calculated as 6.23 and 5.93 Å, respectively. The lattice mismatching rate is calculated to be only 4.81% at room temperature so that MAPbI 3 singlecrystal films (SCFs) are able to be epitaxially grown on MAPbBr 3 single crystal substrate (Wang et al, 2020;Xu et al, 2020). Here in this work, Different from reported solution-processed epitaxy, such as spin-coating method, our work directly put MAPbBr3 substrates into MAPbI 3 precursor solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylammonium lead halide perovskites (MAPbX 3 , where X = Cl, Br, I) have been the most widely studied OIHPs (Wei et al, 2017;Jiang et al, 2019) and the lattice parameters of MAPbI 3 and MAPbBr 3 are calculated as 6.23 and 5.93 Å, respectively. The lattice mismatching rate is calculated to be only 4.81% at room temperature so that MAPbI 3 singlecrystal films (SCFs) are able to be epitaxially grown on MAPbBr 3 single crystal substrate (Wang et al, 2020;Xu et al, 2020). Here in this work, Different from reported solution-processed epitaxy, such as spin-coating method, our work directly put MAPbBr3 substrates into MAPbI 3 precursor solution.…”
Section: Introductionmentioning
confidence: 99%
“…As a new generation of promising semiconductor materials, solution-processable OIHPs are low-cost and have high absorption coefficient, tunable bandgap and long carrier lifetime and diffusion length (Xing et al, 2014;Fang et al, 2015;Wei et al, 2017). Up to now, not only devices based on perovskite single crystals (PSCs) have been widely used but also perovskite films (PFs)-based devices have shown great potential for high-performance photodetectors for visible light, near-infrared light and high energy ray (Shao et al, 2014;Kim et al, 2017;Wang et al, 2018Wang et al, , 2020. For example, Kim et al (2017) used MAPbI 3 films for large-area, low-dose X-ray imaging, Ji et al (2018) reported OHIPs films-based photodetectors with highperformance and Hou et al (2020) reported narrowband photodetectors based on mixed halide PFs.…”
Section: Introductionmentioning
confidence: 99%
“…, where a1 and a2 are the lattice constants of the substrate and epitaxial layer, respectively) are approximately 0.41% and 0.25% for p-type/intrinsic and n-type/intrinsic, respectively, which are good enough for epitaxial growth 40 To design the energy structure of the X-ray PIN photodiode, the band gap of each layer was investigated by absorption spectroscopy, the results of which are shown in Supplementary Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…. PbS and MAPbCl0.5Br2.5 single crystal have a Pb-Pb distance of 5.91 Å and 5.73 Å, respectively (1,13,23,27). PbS possesses similar crystal structure and low lattice mismatch (less than 3.5%) in comparison with those of MAPbCl0.5Br2.5 single crystal, which suggests that highquality epitaxial interface between PbS QDs and MAPbCl0.5Br2.5 single crystal can be formed.During the fabrication of an optoelectronic device, the long OA ligands are replaced by short organic or inorganic ligands to decrease the distance between the QDs and meanwhile efficiently passivate the traps on QDs surface, facilitating transporting and collecting of photoinduced charge carrier in the device.…”
mentioning
confidence: 93%
“…(6,22) PbS quantum dots (QDs) were successfully embedded in MAPbCl0.5Br2.5 single crystal by solution-processed epitaxial growth. (23)(24)(25)(26) Typically, the intrinsic material properties and optoelectronic properties of the MAPbCl0.5Br2.5 with PbS QDs composite crystals were investigated. Due to superior surface states in view of epitaxially matched interface between MAPbCl0.5Br2.5 perovskite and PbS QDs materials, the composite crystals combine the advantages of each: QDs sensitization (bandgap tunability) and the excellent carrier transport properties with low-trap density and high mobility of organohalide perovskites.…”
Section: Introductionmentioning
confidence: 99%